Intellectual Capital Disclosure Practices: An Empirical study on Companies Listed on Colombo Stock Exchange. - Larojan, C.; Fernando, A.J. (Academy for Global Business Advancement, Malaysia, 2016)
Intellectual capital [IC] is regarded as a strategic asset of firms, which is potential of creating value. However, the measurement of intellectual capital is extremely difficult and as a result mere disclosure of IC information in annual reports do not show the impact of value of IC in the financial position of a firm. Main objectives of this study are to develop an IC disclosure (ICD) index to measure the extent and quality of ICD and to examine determinants of ICD practices and their impact on ICD practices based on 50 companies listed on Colombo Stock Exchange (CSE) for the period from 2010 to 2014 by using a content analysis and questionnaire survey. Companies were selected in the order of market capitalization and the data was collected from annual reports. 20 disclosure items representing Internal Capital Disclosure (InCD), External Capital Disclosure (ECD) and Human Capital Disclosure (HCD) are included in the index. Data was analyzed using parametric tests, correlations and panel regression analysis based on pooled regression. Study finds that that there was a common increasing trend for disclosure of IC items and categories. Majority of listed companies disclose IC different forms such as text, sentences, pictures, tables and graphs in line with core discipline of Global Reporting Initiative [GRI] guidelines. ECD was mostly reported in the annual reports followed by HCD and InCD. Theoretical framework of the study takes into account agency theory, stakeholder theory, legitimacy theory and signaling theory. The study offers an insight to the corporate and business level managers, policy makers, potential investors and future researchers regarding ICD practices in terms of extent and quality.
Keywords: Intellectual Capital Disclosures (ICD); Human Capital Disclosure; External Capital Disclosure; Annual Reports; Content Analysis